Dywagacje na temat zasady jedności władzy państwowej - Ławniczak, Artur (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Traditional alternative for popular in our times idea of state power’s dispersion is authority’s concentration in one centre. This solution we can describe as natural, especially in early period of statehood. Then typical phenomenon is monarchy. Thanks for hereditary principle monocratism was lege artis transferred from one generation to another. Later the mankind entered in the time of democracy and republic, but it is impossible completely annihilate monocratic principle, indispensable for each state. In modern epoch monocracy has especially strong position in socialist democracy, where officially sovereign People transfers constitutional power to Parliament and in legislative majority constantly possess Party. Party’s Leader becomes incarnation of contemporary monocracy, in weaker version also in liberal version of democracy, where you can find such organs as President or Prime Minister.
Keywords: state; unity; monocracy; power